PERANAN HAKIM DALAM PENERAPAN PEMBALIKAN BEBAN PEMBUKTIAN DI PERSIDANGAN TINDAK PIDANA PENCUCIAN UANG - Dhian Prismanatha, I Gusti Ngurah; Oka Parwata, Anak Agung Gede (Kertha Wicara : Journal Ilmu Hukum, 2015)
This article discusses the role of judges in the application of the reversal of the burden of proof in proceedings of money laundering . How the role of judges in the application of reversal of the burden of proof in proceedings of money laundering . By using normative research methods , showed that the judge ordered the defendant in order to prove that the assets associated with the case not from or related to the crime referred to in article 2, paragraph 1 of Law No. 8 of 2010 on Money Laundering.
Keywords: Role, Judge, Proof, Money laundering